Comparison of volatile compounds and fatty acids of jujubes (Ziziphus jujuba mill.) before and after blackening process. Issue 1 (31st December 2022) - Song, Yaru; Wang, Fangzhou; Zhang, Rentang; Vidyarthi, Sriram K.; Sun, Xin; Pan, Zhongli
ABSTRACT: Blackened jujube, as an emerging fruit processed product, was obtained from red jujube by a blackening processing of Maillard reaction with high humidity and temperature. This study was to compare the volatile compounds (VOCs) and fatty acids (FAs) between red jujubes (RJs) and blackened jujubes (BJs) of six cultivars (JZ, MZ, JSXZ, HZ, YHDZ and TZ) using headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) and GC-MS respectively. A total of 56 VOCs were detected in these six cultivars (RJs and BJs), and their types and contents were analyzed. A total of 22 FAs, including 12 saturated fatty acids (SFAs) and 10 unsaturated fatty acids (USFAs), was determined in the RJs and BJs, The content of essential FAs in BJs was higher. B-JZ had the greatest increase in linoleic and ɑ-linolenic from 5.3 mg/100 g to 10.0 mg/100 g and from 3.4 mg/100 g to 5.1 mg/100 g, respectively. It indicated that JZ is better for improving flavor and the composition of FAs by blackening process than other five cultivars. In addition, FAs and VOCs were found to have a linear correlation with color. The types of VOCs and FAs between red and blackened jujubes were also discriminated using principal component analysis (PCA).